2016
DOI: 10.1016/j.celrep.2016.02.064
|View full text |Cite
|
Sign up to set email alerts
|

The Innate Immune Receptor NLRX1 Functions as a Tumor Suppressor by Reducing Colon Tumorigenesis and Key Tumor-Promoting Signals

Abstract: SUMMARYNOD-like receptor (NLR) proteins are intracellular innate immune sensors/receptors that regulate immunity. This work shows that NLRX1 serves as a tumor suppressor in colitis-associated cancer (CAC) and sporadic colon cancer by keeping key tumor promoting pathways in check. Nlrx1−/− mice were highly susceptible to CAC, showing increases in key cancer-promoting pathways including nuclear factor κB (NF-κB), mitogen-activated protein kinase (MAPK), signal transducer and activator of transcription 3 (STAT3),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 64 publications
2
58
0
Order By: Relevance
“…In addition to our current findings, prior studies have also evaluated NLRX1 in cancer utilizing either xenograft models or models of inflammation driven colorectal cancer [16, 17, 25, 26]. In the xenograft study, nude mice were injected with RKO colon carcinoma cells, where NLRX1 was either stably knocked down or overexpressed [16].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In addition to our current findings, prior studies have also evaluated NLRX1 in cancer utilizing either xenograft models or models of inflammation driven colorectal cancer [16, 17, 25, 26]. In the xenograft study, nude mice were injected with RKO colon carcinoma cells, where NLRX1 was either stably knocked down or overexpressed [16].…”
Section: Discussionmentioning
confidence: 78%
“…In the presence of TNF, NLRX1 knockdown resulted in significantly increased tumor volume, whereas overexpression attenuated tumor growth [16]. To evaluate the role of NLRX1 in CAC, tumorigenesis was induced in wild type and Nlrx1 −/− mice by treating the animals with the chemical carcinogen azoxymethane (AOM) immediately prior to dextran sulfate sodium (DSS) exposure [17, 25, 26]. In this model, inflammation associated with DSS exposure functions as a tumor promoter.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have emerged that reveal a more dynamic role for NLRX1 in modulating pathological conditions that extend beyond specific host-pathogen interactions (11, 18, 32). To date, there have been very few studies evaluating NLRX1 function in the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…For example, recent evidence has suggested that NLRC3 can also act as a negative regulator of the PI3K-mTOR pathway in epithelial cells, which is involved in colorectal carcinogenesis(26) as well as affecting the type I interferon and proinflammatory pathways. Likewise, NLRX1 has been shown to be involved in negatively regulating multiple tumorigenic pathways(2729) as well as other inflammatory pathways(23, 28, 3032). These recent advances in the field have challenged the model that single NLR proteins are pathogen or pathway specific.…”
Section: Introductionmentioning
confidence: 99%